Coming from the Subway : New York Graffiti Art. - Groninger Museum, Groningen (Groningen : Groninger Museum, 1992)
A-One ; Blade ; Blast, Bill ; Crash ; Daze ; White, Dondi ; Futura ; Haring, Keith ; Koor ; Lee ; Noc167 ; Phase 2 ; Lady Pink ; Quik ; etc.
Coming from the Subway - New York Graffiti Art, Groninger Museum, Groningen, 4 oktober 1992 tot 10 januari 1993
boek